Mouse embryo phenotyping with optical coherence tomography - Scully, Deirdre M.; Larina, Irina V. (Frontiers in Cell and Developmental Biology, 2022)
With the explosion of gene editing tools in recent years, there has been a much greater demand for mouse embryo phenotyping, and traditional methods such as histology and histochemistry experienced a methodological renaissance as they became the principal tools for phenotyping. However, it is important to explore alternative phenotyping options to maximize time and resources and implement volumetric structural analysis for enhanced investigation of phenotypes. Cardiovascular phenotyping, in particular, is important to perform in vivo due to the dramatic structural and functional changes that occur in heart development over relatively short periods of time. Optical coherence tomography (OCT) is one of the most exciting advanced imaging techniques emerging within the field of developmental biology, and this review provides a summary of how it is currently being implemented in mouse embryo investigations and phenotyping. This review aims to provide an understanding of the approaches used in OCT and how they can be applied in embryology and developmental biology, with the overall aim of bridging the gap between biology and technology.